Identification of factors associated with high-cost use of inpatient care in chronic kidney disease: a registry study - P. Marcin Sowa; Sree K. Venuthurupalli; Wendy E. Hoy; Jianzhen Zhang; Anne Cameron; Helen G. Healy; Luke B. Connelly (BMJ Open)
Objective To explore factors behind inpatient admissions by high-cost users (HCUs) in pre-end-stage chronic kidney disease (CKD).Design Retrospective analysis of CKD.QLD Registry and hospital admissions of the Queensland Government Department of Health recorded between 1 July 2011 and 30 June 2016.Setting Queensland public and private hospitals.Participants 5096 individuals with CKD who consented to the CKD.QLD Registry via 1 of 11 participating sites.Main outcomes Associations of HCU status with patient characteristics, pathways and diagnoses behind hospital admissions at 12 months.Results Age, advanced CKD, primary renal diagnosis, cardiovascular disease and hypertension were predictors of the high-cost outcome. HCUs were more likely than non-HCUs to be admitted by means of episode change (relative risk: 5.21; 95% CI 5.02 to 5.39), 30-day readmission (2.19; 2.13 to 2.25), scheduled readmission (1.29; 1.11 to 1.46) and emergency (1.07; 1.02 to 1.13), for diagnoses of the nervous (1.94; 1.74 to 2.15), circulatory (1.24; 1.14 to 1.34) and respiratory (1.2; 1.03 to 1.37) systems and other factors influencing health status (1.92; 1.74 to 2.09).Conclusions The high relevance of episode change and other factors influencing health status revealed that a substantial part of excess demand for inpatient care was associated with discordant conditions often linked to frailty, decline in psychological health and social vulnerability. This suggests that multidisciplinary models of care that aim to manage discordant comorbidities and address psychosocial determinants of health, such as renal supportive care, may play an important role in reducing inpatient admissions in this population.